Do financial development, urbanization, economic growth and renewable energy promote the emission mitigation agenda of Africa? Evidence from models that account for cross-sectional dependence and slope heterogeneity - Kong, Yusheng; Donkor, Mary; Jin, Cheng; Musah, Mohammed; Nkyi, Joseph Akwasi (Frontiers in Environmental Science, 2024)
Carbon emissions from anthropogenic human activities are viewed as the major cause of pollution in the environment. The Paris Treaty came into effect to help minimize the galloping rate of global ecological pollution. The surge in global emissions has prompted other nations to change their environmental regulations to help them to attain their emission mitigation agenda. For instance, China, United States and India have improved their Nationally Determined Contributions they pledged as signatories to the Paris Accord to help them to achieve their sustainable development goals But, despite nations committing to the guidelines of this accord, ecological contamination continues to rise in the globe. To help curb the above menace, a study on the connection between financial development, urbanization, economic growth, renewable energy consumption, and environmental quality of 27 countries from North, South and East Africa over the period 1990 to 2019 was conducted. In attaining this goal, econometric techniques that are robust to heterogeneity and residual cross-sectional dependence were deemed appropriate. From the preliminary analysis, the panel was heterogeneous and cross-sectionally dependent. Also, all the series were stationary after first difference and cointegrated in the long-run. On the regression estimates via the common correlated effects mean group technique, financial development improved environmental quality in the North, South and Eastern regions by 0.56%, 0.42%, and 0.44% respectively. Also, renewable energy promoted ecological safety in the Northern and Eastern regions by 0.24% and 0.08% respectively, but degraded environmental sustainability in the Southern region by 0.66%. Besides, economic growth deteriorated the environment in the North by 0.66%, South by 0.41%, and East by 0.25%. However, urbanization enhanced ecological safety in the East by 0.63%, but had immaterial effect on environmental quality in the North and Southern regions of Africa. Some of the aforestated results are consistent to those under the dynamic common correlated effects mean group (DCCEMG) technique as an alternative estimator. Policy recommendations to help advance the carbon-neutrality target of the regions were proposed.